Light-assisted hierarchical intratumoral penetration and programmed antitumor therapy based on tumor microenvironment (TME)-amendatory and self-adaptive polymeric nanoclusters. (October 2020) - Yan, Jing; Wu, Qinghua; Zhao, Ziyin; Wu, Jianhua; Ye, Huan; Liang, Qiujun; Zhou, Zhuchao; Hou, Mengying; Li, Xudong; Liu, Yong; Yin, Lichen
Abstract: The anticancer performance of nanomedicine is largely impeded by insufficient intratumoral penetration. Herein, tumor microenvironment (TME)-amendatory and self-adaptive nanoclusters (NCs) capable of cancer-associated fibroblasts (CAFs) depletion and size/charge conversion were engineered to mediate light-assisted, hierarchical intratumoral penetration. Particularly, large-sized NCs ( 50 nm) were prepared via self-assembly of FAP-α-targeting peptide-modified, 1 O2 -sensitive polymers, which were further used to envelope small-sized dendrimer ( 5 nm) conjugated with Ce6 and loaded with DOX (DC/D). After systemic administration, the NCs efficiently targeted CAFs and generated lethal levels of 1 O2 upon light irradiation, which depleted CAFs and concomitantly dissociated the NCs to liberate small-sized, positively charged DC/D. Such stroma attenuation and NCs transformation collectively facilitated the delivery of DC/D into deeper regions of CAF-rich tumors, where DOX and 1 O2 provoked synergistic anti-cancer efficacies. This study provides an effective approach to facilitate the tumor penetration of nanomedicine by concurrently and spatiotemporally reconfiguring the nano-properties and remodeling the TME. Graphical abstract: Image 1